Praktik Pemotongan Berat Timbangan pada Akad Jual Beli Cengkeh Kering: Perspektif Bisnis Islam - Umagapi, Aidia; Hamizar, Arizal; Karnudu, Fitria (Universitas Islam Raden Rahmat, 2024)
This research aims to look more deeply into the phenomenon of sale and purchase dried cloves in Fagudu Village. Some of the clove buyers often cut off the weight that has been weighed, which has become a habit in the market. The type of research used in this study is field research with a qualitative approach. As a single case study, this research was carried out in Fagudu Village, Sula Islands Regency, North Maluku Province, using data collection methods in the form of interviews, observation, and documentation. The data obtained is then analysed by reducing the data, displaying the data, and drawing conclusions. Based on the research results, it is known that the practice of cutting the weight of the scales in the sale and purchase agreement for dried cloves in Fagudu Village was carried out after there was an agreement between the traders and sellers and was carried out on a consensual basis. From the perspective of Islamic Economics, the practice of cutting the weight of the scales, which has become a habit of the Fagudu Village community, does not conflict with Islamic teachings. This is because the cutting is done after there is agreement or willingness from both parties, so there is no element of coercion in it.